Socialization of The Abuse and Danger of Formaline as A Preservative in Food Materials at Lubuk Pakam District - Sinurat, Jhon Patar; Br Karo, Reh Malem; Syarifuddin, Shofian (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
The addition of formalin is often misused by making it a food preservative. This happens because the price of formalin is cheaper than natural food preservatives and synthetic food preservatives. Despite realizing that formalin is very dangerous because it is carcinogenic and irritating to the body. Food ingredients containing formaldehyde are commonly found in tofu and meatball products. While meatballs and years are food ingredients that are much liked by the community. Both types of food contain lots of protein and carbohydrates which are good for health. Community service activities are carried out through outreach activities using lectures, discussion, and question-and-answer methods. The number of participants who participated in this PkM activity was 20 people aged in the 25-45 year range who were in the Lubuk Pakam sub-district. This PkM activity uses a system of pre-test and post-test in evaluating the level of increase in participants' knowledge. In addition, the level of satisfaction of participants in PkM activities was measured using a questionnaire. The results of the service show that PkM activities have provided additional knowledge to the community so that they are more careful in choosing food ingredients for consumption so that they will avoid the dangers of misuse of formaldehyde in food. Based on the evaluation carried out on the PkM activities, there was an increase in the average knowledge of the PkM participants by 30% after being given socialization. While the majority of 95% (19 PkM participants) were satisfied with the implementation of this PkM activity.